1977
DOI: 10.1017/s0022029900019890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, dietary protein and weaning on calf abomasal enzymic secretion

Abstract: Using fistulated calves, the influence of the age, type of dietary protein and weaning on the secretion of chymosin and pepsin by the abomasum were studied. The abomasum secreted both chymosin and pepsin when the animals were fed milk. Chymosin secretion appeared to be independent of the age of the animals, whereas a slow increase in pepsin secretion was observed as the calves aged. Several preruminant animals were fed either a skim-milk diet or a milt substitute in which proteins were provided by fish, soya o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

1980
1980
1997
1997

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…The ratios of the enzymes in the present material are shown in Table 1. DISCUSSION The secretion of chymosin from the gastric mucosa is highly correlated with milk-feeding and age (Garnot et al 1977;Andren et al 1980Andren et al , 1981 Several workers (Corpron, 1966;Rubin, Ross, Sleisenger & Jeffries, 1968;Matsuyama & Suzuki, 1970) have suggested that the mucous neck cell is the precursor of the chief cell, and Kataoka (1970) observed groups ofimmature chiefcells in the upper part of the base in gastric glands of the mouse. If this is so, the following hypothesis might explain the lack ofprochymosin-containing chief cells in the lower base of older animals (see also Fig.…”
Section: Rocket Immunoelectrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…The ratios of the enzymes in the present material are shown in Table 1. DISCUSSION The secretion of chymosin from the gastric mucosa is highly correlated with milk-feeding and age (Garnot et al 1977;Andren et al 1980Andren et al , 1981 Several workers (Corpron, 1966;Rubin, Ross, Sleisenger & Jeffries, 1968;Matsuyama & Suzuki, 1970) have suggested that the mucous neck cell is the precursor of the chief cell, and Kataoka (1970) observed groups ofimmature chiefcells in the upper part of the base in gastric glands of the mouse. If this is so, the following hypothesis might explain the lack ofprochymosin-containing chief cells in the lower base of older animals (see also Fig.…”
Section: Rocket Immunoelectrophoresismentioning
confidence: 99%
“…If it is possible to stimulate prochymosin production in older calves by milk-feeding, the stimulus from milk in this experiment probably was too low to induce more than a few mucous neck cells to differentiate into chief cells producing both proenzymes. One reason for this might have been that the milk was entering the rumen instead of the abomasum, as a consequence of an incomplete closure of the oesophageal groove, thereby not providing enough stimulus for the prochymosin production (Garnot et al 1977;Andren et al 1981).…”
Section: Rocket Immunoelectrophoresismentioning
confidence: 99%
“…Gastric proteolysis is due to pepsins and chymosin (Berridge et al, 1943 ;Garnot et al, 1977). It has been shown that these enzymes rapidly cleave the Phe 105-Met 106 bond in x-casein (Delfour, Alais and Jolles, 1966) and that this single splitting is responsible for milk clotting.…”
mentioning
confidence: 99%
“…It has been considered that, although the quantity of pepsin is very low in this stomach compartment of milk-fed calves, it has appreciable activity (Berridge et al, 1943 ;Garnot et al, 1977 ;Guilloteau et al, 19831. ln vitro proteolysis of casein by chymosin or pepsins is relatively well known (Delfour, Alais and Jolles, 1966 ;Fox and Walley, 1971 ;Creamer, Mills and Richards, 1971 ;Hill, Lahav and Givol, 1974 ;P61issier, Mercier and RibadeauDumas, 1974 ;Visser and Slangen, 1977 ;Fox, 1977, 1979a, b ;Addeo, P61issier and Chianese, 1981 ;Visser, 1981 proteolysis of milk-proteins in the stomach. These studies deal with gastric emptying in rats (Zebrowska, 1968 ;Buraczewski et al, 1971 ;P61issier, 1981, 1983), pigs (Braude et al, 1970a, b) and calves (Toullec, Thivend and Mathieu, 1971 ;Ternouth and Roy, 1973 ;Guilloteau et al, 1975Guilloteau et al, , 1979P61issier et al, 1983) fed with milk or casein diets.…”
mentioning
confidence: 99%